Konsep Manajemen dalam al-Qur’an - Hidayat, Syarif (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
The purpose of this research is to describe the concept of management in the Qur'an. Library studies are used as a method of research by referencing several sources from scientific books and journals. The results of the discussion concluded that the forms of the concept of management are found in the Qur'an which is grouped into the form of fi'il mudhari', af'alul khomsah, jama' mudzakkar, and isim fa'ail. The basics of Islamic management contained in the Qur'an are justice, trust and accountability, and communication. Management principles include amar ma'ruf nahi munkar, the obligation to uphold truth and justice and deliver a mandate